Analysis of Seagrass Condition Thalassia hemprichii in Kabung Island Waters, Bengkayang Regency, West Kalimantan - Mega Sari Juane Sofiana; Ikha Safitri; Risko Risko; Karina Elwanda Saputri; Taufik Nurcahyanto (JURNAL PERIKANAN DAN KELAUTAN, 2020)
Seagrass is one of the important ecosystems and habitats for marine organisms. Thalassia hemprichii is one of the seagrass species in Kabung Island Waters. Studies on seagrass ecosystem conditions must be carried out as initial information for integrated aquatic management. Analysis of seagrass ecosystem conditions includes density and coverage percentage. Seagrass data was collected using the line transect method with a length of 50 cm and quadrants transect of 1 m x 1 m perpendicular to the coastline toward the sea. The density of T. hemprichii at Stations I and II were 50.83 and 68.27 ind/m2, respectively. The average coverage percentage at Stations I and II were 5.05% and 5.85%, respectively. These ecosystem conditions could be categorized as rare density. Physico-chemical parameters of the waters of Kabung Island including temperature, salinity, pH, dissolved oxygen (DO), water visibility, depth, and current have been carried out. The Kabung Island waters have a salinity of 32-33‰, temperature 29-30oC, and pH 8.0-8.4. The depth and water visibility of the seagrass habitat was 0.6 m. The current velocity was 0.07-0.29 m/s. These parameters were optimum conditions for seagrass life. However, the dissolved oxygen in Kabung Island was low at 2.2-4 mg/L.